ANALISIS MULTIKRITERIA UNTUK MEMETAKAN DAERAH RENTAN BANJIR PADA SUB DAS BUAH, PALEMBANG - Sartika Nisumanti; Yulyana Aurdin (Jurnal Tekno Global, 2018)
Flooding is a serious problem for last time that hit several regions in Indonesia, either urban or rural areas. Palembang city suffered  a loss of nearly 1.5 billion dollars per year, due to damage to public infrastructure and households, especially in low lying areas, such as Bendung watershed, Buah watershed, and Lambidaro watershed (Putranto and Popy, 2009, Hamiem, 2012). Almost 52% of the area of Palembang City is a swamp area with some type of swamp, marsh are flooded throughout the year, shortly stagnant swamp when it rains, flooded swamps and tidal current occurs. To map areas vulnerable to inundation or flooding in the sub watershed system, the analysis needs to be performed using a multi criteria approach of some of the parameters that affect flooding. For the analysis problem in susceptible areas to flooding in the Buah subwatershed. The results of this study showed  that the inundation height of 20-40 cmand a pool of up to 3 hours long. Location inundation accurred in Jalan Urip Sumoharjo close to residential Ajendam, Kenten Permai, SMU Bina Warga, Rama Kasih, Griya Sekojo and mosque of Arafura. Results of Multi-Criteria analysis to show the distribution of vulnerable runoff coefficient of 0.7, which means rainfall that falls to just 30% Buah Watershed whereas infiltered into the runoff by 70%.Keywords : Multi-spatial, Flood, DUFLOW, early warning